2011
DOI: 10.1093/nar/gkr1076
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure of adenovirus DNA throughout infection

Abstract: For more than half a century, researchers have studied the basic biology of Adenovirus (Ad), unraveling the subtle, yet profound, interactions between the virus and the host. These studies have uncovered previously unknown proteins and pathways crucial for normal cell function that the virus manipulates to achieve optimal virus replication and gene expression. In the infecting virion, the viral DNA is tightly condensed in a virally encoded protamine-like protein which must be remodeled within the first few hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 84 publications
(132 reference statements)
1
83
0
Order By: Relevance
“…The final components of the HAdV-2 ϳ150-MDa mature particle include multiple copies of seven different proteins in the icosahedral shell (hexon, penton base, fiber, IIIa, VI, VIII, and IX) and three putative DNA condensing proteins bound to the genome in the core (V, VII, and ) (41,42). In addition, several other factors are required to assemble the fully infectious particle.…”
Section: Discussionmentioning
confidence: 99%
“…The final components of the HAdV-2 ϳ150-MDa mature particle include multiple copies of seven different proteins in the icosahedral shell (hexon, penton base, fiber, IIIa, VI, VIII, and IX) and three putative DNA condensing proteins bound to the genome in the core (V, VII, and ) (41,42). In addition, several other factors are required to assemble the fully infectious particle.…”
Section: Discussionmentioning
confidence: 99%
“…How viruses resist cellular chromatinization and silencing is known for only a few viruses (9,12,13). These include herpes simplex viruses (HSVs) (14)(15)(16), polyomaviruses (17,18), adenoviruses (19), and cytomegaloviruses (20,21), all of which encode proteins that promote transcriptionally activating histone modifications on chromatinized viral genomes during lytic infection.…”
Section: Viral Dna Introduced Into Cell Nuclei Is Exposed To Cellularmentioning
confidence: 99%
“…Pre-viously, we identified host cell-derived remodeling factors for Ad chromatin by biochemical analyses (19,22,24,26) and demonstrated that TAF-I, one of these host factors, plays an important role in the regulation of viral early gene expression in infected cells through interactions with protein VII (15,17,18,20,27). Thus, it was indicated that the remodeling of Ad chromatin is a crucial process for its genome functions (13), as is the case for the cellular genome. In addition, using chromatin immunoprecipitation (ChIP) assays, we recently reported that in early phases of infection, cellular histones are incorporated into viral DNA-protein VII complexes and that a histone modification occurs depending upon the transcription states on viral chromatin, suggesting that cellular histones could be functional components of viral chromatin in infected cells (20).…”
mentioning
confidence: 97%